Solving problems of dangerous geophysical phenomena monitoring by the geophysical equipment of the Ukrainian Antarctic Base “Akademik Vernadsky” - A. I. Liashchuk; V. Pavlovych (Ukrainian Antarctic Journal, 2010)
The results of the conducted works on complex processing of geophysical information are presented in the article. A purpose of processing is revealing of the dangerous geophysical phenomena in the Antarctic peninsula region. The analysis of possible mechanism of forming of earthquake precursors is performed. It is possible that the cause of anomalous signals is a tectonic waves appearing due to preparation of strong earthquakes at the distant centers.